War against Islamic State : sowing seeds of more extremist group - James M. Dorsey (2014)
The US-led war against the Islamic State, the jihadist group that controls a swath of Syria and Iraq, is sowing seeds for the sprouting of yet more extremist groups. In doing so the US is reverting to a misguided policy that has spawned more virulent forms of militant Islam.